2022
DOI: 10.2147/cia.s346824
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia Management and Outcomes in Elderly Stroke Patients with Malnutrition Risk: Results from Chinese Stroke Center Alliance

Abstract: Purpose To investigate the effectiveness of dysphagia screening and subsequent swallowing rehabilitation in elderly stroke patients with malnutrition risk. Patients and Methods Based on the Chinese Stroke Center Alliance (CSCA) from August 1, 2015 to July 21, 2019, we compared the in-hospital adverse outcomes among stroke patients (including ischemic stroke, intracranial hemorrhage, and subarachnoid hemorrhage) over 70 years old with and without dysphagia screening. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
4
0
3
Order By: Relevance
“…This in turn leads to a decrease in serum albumin levels. The presence of malnutrition can further deteriorate the patient’s physiological state and negatively impact neurological function, thereby increasing the risk of delirium [ 44 ]. Wang et al demonstrated that early implementation of protein supplementation effectively reduced mortality in critically ill stroke patients, underscoring the importance of ensuring adequate nutritional availability for the management and recovery of acutely ill patients [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This in turn leads to a decrease in serum albumin levels. The presence of malnutrition can further deteriorate the patient’s physiological state and negatively impact neurological function, thereby increasing the risk of delirium [ 44 ]. Wang et al demonstrated that early implementation of protein supplementation effectively reduced mortality in critically ill stroke patients, underscoring the importance of ensuring adequate nutritional availability for the management and recovery of acutely ill patients [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this vicious circle between dysphagia, malnutrition, and muscle atrophy may result in easy development of sarcopenia. After the stroke onset, malnutrition occurs in 8.2–49.% patients, and dysphagia occurs in 24.3–52.6% ( 40 ). Nasogastric feeding was significantly associated with sarcopenia after adjusting for sex, age, NIHSS, the cognitive level, complications, comorbidity, rehabilitation time, and time from the stroke onset to hospitalization ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the clinical quality indicators, 12 related to safety and referred to the management of stroke risk factors and complications and included the indicator with the highest frequency of occurrence (19): dysphagia screening 19 28–31 34–41 43 45–49. Four indicators were grouped under effectiveness to assess health outcomes or achieve a care or service objective.…”
Section: Resultsmentioning
confidence: 99%